Influence of operating parameters on biomass conversion under suband supercritical water conditions - Md Isa, Khairuddin; Farizul Hafiz , Kasim; Saiful Azhar , Saad; Mohd Asri , Ab Rahim; Abd Aziz, Mohd Aizudin; Md Ali, Umi Fazara (Wiley-VCH Verlag, 2017)
The influence of reaction pressure, reaction time, reaction temperature, and biomass- to-water mass ratio R on the conversion of miscanthus biomass to biofuels under sub- and supercritical water (SCW) conditions was investigated. The highest total conversion was obtained under SCW conditions and the heating value increased under subcritical and SCW conditions. The findings herein show that near-supercritical and supercritical water at 400C and high pressure can be an effective reaction medium for converting biomass to oils with relatively low oxygen contents in high yields.